EVALUATING CARBON CAPTURE AND STORAGE IN A CLIMATE MODEL WITH ENDOGENOUS TECHNICAL CHANGE - Durmaz, Tunc; Schroyen, Fred (WORLD SCIENTIFIC PUBL CO PTE LTD, 2020)
We assess the extent to which Carbon Capture and Storage (CCS) and R&D on this abatement technology are part of a socially efficient solution to the problem of climate change. For this purpose, we extend the intertemporal model of climate and directed technical change developed by Acemoglu et al. (2012) [The environment and directed technical change. American Economic Review, 102(1), 131-166] to include a sector responsible for CCS. We show that two types of solutions exist: a renewable energy regime where current CCS technology is only temporarily used but never further developed; and a fossil energy regime where CCS is part of a long-term solution and is further developed at about the same rate as fossil energy technology. Our computations show that for current estimates of the marginal cost of CCS, the renewable energy regime clearly dominates the fossil fuel energy regime.
Keywords: Carbon capture and storage; renewable energy; fossil fuel energy; endogenous technical change; climate change; RESEARCH-AND-DEVELOPMENT; TECHNOLOGICAL-CHANGE; ENVIRONMENTAL-POLICY; CO2 ABATEMENT; GROWTH; TAXES; COSTS; SEQUESTRATION; OPTIONS; ENTICE; Business & Economics; Environmental Sciences & Ecology